2011
DOI: 10.1177/097206341101300404
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, Health Expenditure and Willingness to Pay for Health Insurance amongst the Urban Poor

Abstract: The study aimed to assess the demand for health insurance, gather evidence on willingness to pay (WTP) for health insurance and its determining factors amongst the urban poor in Mumbai. This was as-certained through dichotomous bidding process on 300 households (HHs). The findings reveal characteristics of a low-income group with a burden of disease and treatment financed through out-of-pocket (OOP) expenditure, which is at times catastrophic. These factors justify the demand for health care insurance in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
3
24
1
Order By: Relevance
“…Similarly, Asfaw et al found that a 1% increase in income in rural Ethiopia led to an 8.4% increase in the probability of willingness to pay for health insurance 30 . In India, households in the highest wealth quintile were 2.1 times more willing to pay for CBHI compared with those in the lowest quintile 33 . Similarly, in China, Zhanga et al found that willingness to join a CBHI program increased by 0.83% to 1.54% when income increased by 100 Yuan in a year.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, Asfaw et al found that a 1% increase in income in rural Ethiopia led to an 8.4% increase in the probability of willingness to pay for health insurance 30 . In India, households in the highest wealth quintile were 2.1 times more willing to pay for CBHI compared with those in the lowest quintile 33 . Similarly, in China, Zhanga et al found that willingness to join a CBHI program increased by 0.83% to 1.54% when income increased by 100 Yuan in a year.…”
Section: Resultsmentioning
confidence: 96%
“…Our academic database searches yielded 1411 hits and the gray literature searches another 8 articles. After screenings of the titles and abstracts, we kept58 studies for full-text review (Fig 1), and thereafter retained 23 articles for detailed review [11][12][13][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Of these, two articles [26] and [20] were excluded after quality assessment.…”
Section: Search Resultsmentioning
confidence: 99%
“…The remaining 21 articles relate to 16 distinct studies in the following ten countries: In Asia: Bangladesh [34], China [27], India [18,19,28,33], Iran [21,32] and Vietnam [12]. In Sub-Saharan African: Burkina Faso [16], Cameroon [22,30], Ethiopia [13], Ghana [11], and Nigeria [17,29].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations